Mengenyahkan Sampah Plastik Benalu dengan Ekobrik: Get Rid of Parasitic Plastic Waste with Ecobricks - Zuska, Fikarwin; Naria, Evi; Zulfendri, Zulfendri (Universitas Medan Area, 2024)
Household plastic packaging waste, which we refer to as 'parasitic plastic' due to its perceived lack of usefulness for business, is generally disposed of by household members without processing. The quantity of this waste throughout Indonesia is very large and continues to increase, in line with household consumption growth. If this parasitic plastic waste continues to be left untreated, it will have long-term impacts on ecology and health; in the short term, it will affect cleanliness and the aesthetics of residential environments. The creation of incentive-based eco-bricks, by stuffing plastic packaging waste into 600 ml bottles weighing around 200 grams, and providing incentives of IDR 3,000 - 5,000 per bottle to participating communities. Additionally, the formation of organized ecobrick groups is a solution that can reduce daily plastic waste from households and decrease the scattered plastic waste that damages environmental aesthetics, cleanliness, and sustainability. Through participatory action methods, it was found that those involved in the creation of incentive-based eco-bricks tend to be predominantly women (housewives) and children from low-income families. Women involved in this activity (in terms of age) generally move slowly but consistently.